2015
DOI: 10.1136/annrheumdis-2014-206927
|View full text |Cite
|
Sign up to set email alerts
|

Synovial tissue volume: a treatment target in knee osteoarthritis (OA)

Abstract: BackgroundSynovitis occurring frequently in osteoarthritis (OA) may be a targeted outcome. There are no data examining whether synovitis changes following intra-articular intervention.MethodsPersons aged 40 years and older with painful knee OA participated in an open label trial of intra-articular steroid therapy. At all time points they completed the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire. They had a contrast-enhanced (CE) MRI immediately prior to an intra-articular steroid injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 13 publications
2
107
0
3
Order By: Relevance
“…Manual segmentation is considered to be an accurate and reliable method for the assessment of synovitis on CE‐MRI, and effusion‐synovitis on noncontrast enhanced MRI, with intraobserver agreement up to 0.94 and 0.97 . Manual segmentation is, however, time‐consuming for the measurement of synovitis and can take between 45 to 120 min per case .…”
Section: Discussionmentioning
confidence: 99%
“…Manual segmentation is considered to be an accurate and reliable method for the assessment of synovitis on CE‐MRI, and effusion‐synovitis on noncontrast enhanced MRI, with intraobserver agreement up to 0.94 and 0.97 . Manual segmentation is, however, time‐consuming for the measurement of synovitis and can take between 45 to 120 min per case .…”
Section: Discussionmentioning
confidence: 99%
“…Men and women aged 40 years and over were recruited from primary and secondary care clinics for participation in an open-label study (TASK)13 looking at the efficacy of intra-articular steroid therapy in symptomatic knee OA (ISRCTN: 07329370). Subjects were included in the trial if they met the American College of Rheumatology (ACR) criteria including moderate knee pain for more than 48 hours in the previous 2 weeks or scored greater than 7 out of 32 on the Knee Injury and Osteoarthritis Outcome Score (KOOS), questions P2 – P9.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that intra-articular steroids relieve pain in part by reducing synovitis within the knee. 3 Ongoing studies are evaluating whether reduction in synovitis can not only reduce pain but also stanch the progression of structural disease. It stands to reason that any treatment targeting inflammation within the joint might be expected to reduce pain and maybe even delay structural deterioration in the diseased joint.…”
Section: David T Felson 12 Heike a Bischoff-ferrarimentioning
confidence: 99%